Pneumococcal carriage in rural Gambia prior to the introduction of pneumococcal conjugate vaccine: a population‐based survey. Issue 7 (6th April 2015) - Usuf, Effua; Badji, Henry; Bojang, Abdoulie; Jarju, Sheikh; Ikumapayi, Usman Nurudeen; Antonio, Martin; Mackenzie, Grant; Bottomley, Christian
Abstract Objective To evaluate pneumococcal colonisation before and after the introduction of pneumococcal conjugate vaccine (PCV) in eastern Gambia. Methods Population‐based cross‐sectional survey of pneumococcal carriage between May and August 2009 before the introduction of PCV into the Expanded Program on Immunization. Nasopharyngeal swabs were collected from all household members, but in selected households, only children aged 6–10 years were swabbed. This age group participated in an earlier trial of a nine‐valent PCV between 2000 and 2004. Results The prevalence of nasopharyngeal pneumococcal carriage in 2933 individuals was 72.0% in underfives (N = 515), 41.6% in children aged 5–17 (N = 1508) and 13.0% in adults ≥18 (N = 910) years. The age‐specific prevalence of serotypes included in PCV7, PCV10 and PCV13 was 24.7%, 26.6% and 46.8% among children <5 years of age; 8.5%, 9.2% and 17.7% among children 5–17 years; and 2.5%, 3.3% and 5.5% among adults ≥18 years. The most common serotypes were 6A (13.1%), 23F (7.6%), 3 (7.3%), 19F (7.1%) and 34 (4.6%). There was no difference in the overall carriage of pneumococci between vaccinated and unvaccinated children 8 years after the primary vaccination with three doses of PCV (48.3% vs. 41.1%). Conclusion Before the introduction of PCV, serotypes included in PCV13 accounted for about half the pneumococcal serotypes in nasopharyngeal carriage. Thus, the potential impact of PCV13 on pneumococcal disease in the Gambia is substantial.